Dark tourism: The effect of visiting a mausoleum on a tourist’s psychological mood state in the central Asian city of Samarkand, Uzbekistan - Patterson, Ian; Vafokulova, Mekhruza; Oblakulov, Bekzod (Journal of Tourism Management Research, 2024)
This paper examines the psychological effects of dark tourism by analyzing the feelings and emotions of domestic and international tourists who visited a mausoleum. Dark tourism sites have received considerable attention as a growing phenomenon in the 21st century. Dark tourism is associated with death, disasters, and atrocities; and includes places such as murder sites, battlefields, cemeteries, and places where tragedies have taken place. The Gur-e-Amir Mausoleum in the Central Asian city of Samarkand in Uzbekistan was chosen as a dark tourism site. A convenience sample of 21 visitors, of which 10 were international travelers and 11 were from Central Asian countries, agreed to be individually interviewed using a qualitative methodology. The results found that a range of emotions were expressed during the visit, with the majority of visitors expressing positive emotions on a scale from good to great, which included feelings of contentment, astonishment, excitement, and admiration at the conclusion of their visit. For many of the local visitors of the Islamic faith, it also provided a religious experience that for, some included prayer and meditation.